2017
DOI: 10.7863/ultra.16.04042
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Distance Between the Distal Rectal Pouch and Perineum From the Birth Day to the Next Day in Neonates With an Imperforate Anus

Abstract: The pouch-perineum distance was shorter on the next day than on the birth day, and the diagnostic performance of the pouch-perineum distance on the next day was significantly superior to that on the birth day for the diagnosis of a low-type imperforate anus. We recommend sonography on the next day in neonates with an imperforate anus when possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 23 publications
(73 reference statements)
0
28
0
Order By: Relevance
“…We report a 40% false‐negative rate for the diagnosis of a low‐type imperforate anus when using only the pouch‐perineum distance on sonography. It has been reported that meconium is produced after birth in neonates with an imperforate anus as well as in healthy neonates . Therefore, the possibility exists that we could not accurately determine the rectal mucosal position as the base of the pouch because of a collapse of the rectal mucosa on the day of birth.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We report a 40% false‐negative rate for the diagnosis of a low‐type imperforate anus when using only the pouch‐perineum distance on sonography. It has been reported that meconium is produced after birth in neonates with an imperforate anus as well as in healthy neonates . Therefore, the possibility exists that we could not accurately determine the rectal mucosal position as the base of the pouch because of a collapse of the rectal mucosa on the day of birth.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the possibility exists that we could not accurately determine the rectal mucosal position as the base of the pouch because of a collapse of the rectal mucosa on the day of birth. Actually, the diagnostic performance for the type of imperforate anus according to the pouch‐perineum distance has been reported to be worse on the day of birth day than on the day after birth . Sonographic examinations performed both on the day of birth and the day after birth were included in our study, which might have accounted for the high false‐negative rate of sonography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations